Lesotho : Lesotho-Staff Report for the 2000 Article IV Consultation and Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2001)
The Lesotho economy is experiencing a downturn of economic growth, high unemployment and poverty, and fiscal and balance-of-payments pressures. The size of the proposed fiscal adjustment is adequate because it focuses on improvement in the external current account balance and the maintenance of gross international reserves. The current monetary arrangement with South Africa has served Lesotho well. The efforts of the central bank to reduce the wide interest rate spreads, encourage financial intermediation, mobilize domestic savings, and reduce capital flight have been commended.